A Longitudinal Investigation on the Relation between Self-Compassion and Alcohol Use in a Treatment Sample: A Brief Report. (February 2020) - Garner, Alisa R; Gilbert, Sarah E; Shorey, Ryan C; Gordon, Kristina C; Moore, Todd M; Stuart, Gregory L
Alcohol misuse is often a chronic problem such that relapses following treatment are common. One potential protective factor for alcohol misuse is self-compassion, which includes self-kindness, feelings of common humanity, and mindfulness when faced with personal suffering and hardships. This study tested the hypothesis that self-compassion, and specifically self-compassion promoting facets including self-kindness, common humanity, and mindfulness, were longitudinally associated with reduced alcohol use among a sample of men and women in substance use disorder treatment ( N = 62). Results partially supported the hypothesis, in that only the mindfulness facet of self-compassion was associated with decreased alcohol use over time. Sex and age differences as they related to the positive facets of self-compassion and alcohol use emerged. These findings suggest that positive facets of self-compassion may be beneficial factors to cultivate in alcohol treatment programs.